How to Read a Book: The Classic Guide to Intelligent Reading - Mortimer J. Adler; Charles Van Doren (New York A Touchstone Book, 2014)
How to Read a Book, originally published in 1940, has become a rare phenomenon, a living classic. It is the best and most successful guide to reading comprehension for the general reader. And now it has been completely rewritten and updated. You are told about the various levels of reading and how to achieve them - from elementary reading, through systematic skimming and inspectional reading, to speed reading, you learn how to pigeonhole a book, X-ray it, extract the author's message, criticize. You are taught the different reading techniques for reading practical books, imaginative literature, plays, poetry, history, science and mathematics, philosophy and social science. Finally, the authors offer a recommended reading list and supply reading tests whereby you can measure your own progress in reading skills, comprehension and speed.
Keywords: Education; Nonfiction; Self Help; Philosophy; Language